Effect of TiO2 Content on the Corrosion and Thermal Resistance of Plasma-Sprayed Al2O3-TiO2 Coatings - Viktorija Grigaitienė; Liutauras Marcinauskas; Airingas Šuopys; Romualdas Kėželis; Egidijus Griškonis (Crystals)
Modern industrial systems and biomass-fired furnaces require surface treatments that can withstand aggressive chemical, thermal, and corrosive environments. This study investigates the corrosion and thermal resistance of plasma-sprayed Al2O3-TiO2 coatings produced using a DC air–hydrogen plasma spray process. Coatings of compositions of Al2O3, Al2O3-3 wt.% TiO2, Al2O3-13 wt.% TiO2, and Al2O3-40 wt.% TiO2 were deposited on steel substrates with a Ni/Cr bond layer by plasma spraying. The coatings were characterized by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) to evaluate their morphology, elemental composition, and crystalline phases. Electrochemical tests were performed in a naturally aerated 0.5 mol/L NaCl solution and cyclic thermal–chemical exposure tests (500 °C using 35% KCl) to assess their corrosion kinetics and thermal stability. The results indicate that pure Al2O3 and low TiO2 (3 wt.%) coatings exhibit fine barrier properties, while coatings with a higher TiO2 content develop additional phases (e.g., Ti3O5, Al2TiO5) that improve thermal resistance but reduce chemical durability.